A Systematic Review: Riset Material Flow Cost Accounting di Indonesia - Imelia Sari; Putri Purnama Dewi; Zul Azmi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study presents a systematic review of 15 research articles on Material Flow Cost Accounting (MFCA) conducted in Indonesia between 2020 and 2025. Using the Systematic Literature Review (SLR) approach, this paper aims to map the development, focus areas, and practical implementation of MFCA within the Indonesian context. The reviewed studies were published in nationally accredited journals SINTA and Scopus. Thematic and bibliometric analyses were applied to identify research trends by topic, method, industrial sector, and findings. The results indicate that MFCA research in Indonesia has grown significantly during the period, with dominant themes related to manufacturing efficiency, green accounting integration, environmental performance, and sustainable development. Most studies confirm that MFCA improves material efficiency, reduces waste, and enhances both economic and environmental performance, particularly when combined with Green Accounting and Environmental Management Accounting (EMA). However, MFCA adoption remains limited due to low managerial awareness, weak accounting information systems, and the absence of national implementation guidelines. This review concludes that MFCA holds strong potential to advance corporate sustainability in Indonesia if supported by institutional commitment, stakeholder collaboration, and digital transformation. Future research should expand MFCA applications in service, agricultural, and cross-industry sectors.